Predictors of re‐excision in wire‐guided wide local excision for early breast cancer: a Western Australian multi‐centre experience. Issue 7 (16th April 2015) - Ballal, Helen; Taylor, Donna B.; Bourke, Anita G.; Latham, Bruce; Saunders, Christobel M.
Abstract: Background: A significant proportion of breast cancers present as impalpable lesions requiring radiological guidance prior to surgical excision, commonly by hook‐wire placement. Complete lesion excision is an essential part of treatment, and re‐excision may be needed to ensure this and minimize local recurrence. We explore a 1‐year audit of re‐excision of hook‐wire‐guided excisions in two large public breast units in Western Australia and define factors associated with the requirement for re‐excision. Methods: A retrospective review of wire‐localized wide local excisions for early breast cancer in 2009 at two tertiary breast centres in Western Australia. Results: Of 148 localized lesions, 44 (30%) underwent re‐excision. The only significant preoperative finding was the location of tumour in the breast. The intra‐operative specimen radiograph provided useful information that influenced re‐excision. Smaller (≤5 mm) and larger (>20 mm) tumours on final pathological size were more likely to undergo re‐excision as well as a larger difference in actual size to predicted size. The presence of ductal carcinoma in situ (DCIS) increased re‐operation, as did multifocality. Conclusion: This study highlights factors that should make the surgeon more cautious for re‐excision. Suspicion of DCIS, especially at the periphery of tumours, and a central tumour location increase risk. Lesion localization techniques play an important role in minimizing risk while maintaining cosmesis.